Strategic Alliance As A Business Strategy In Setting Up A Vaccine Factory (Case Study Of Pt Bandung Vaksin Sentosa) - Brahma, Yoga; Siahaan , Uke Marius; Rahadi , Raden Aswin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
Indonesia, with a population of over 270 million, offers a growing vaccine market, driven by strong immunization programs and post-COVID awareness. CZBP proposes a joint venture with PT BVS to establish a vaccine facility focusing on downstream processes. A financial feasibility study will evaluate investment costs, expected revenue, risks, and the project’s long-term impact on national biopharmaceutical independence. It will also assess repayment capability, funding options, and financing strategies. The project requires IDR 363.69 billion, with the best outcome through a strategic partnership, achieving an NPV of IDR 2.778 trillion, IRR of 45.30%, and a Payback Period of 4.31 years